Vintage Design Furniture in Albania, a New Retro Design Paradigm in the Post-Communist Era (European Journal of Formal Sciences and Engineering, 2019)
The dynamics of the Albanian market in lieu of the multifaceted transformations following the collapse of the communist regime and moving towards the accession processes in the European Union as well as the demographics of the Albanian society as a whole, deeply impact the ways in which furniture products are designed, development and produced. This paper draws from my doctoral study which explored the transformation of furniture products from communism to post-communism. The doctoral study confirmed that: the impact of moving from mass production in a centralized economy to free mass customization in market economy has not radically transformed the fundamental properties of furniture but has affected the design, development, delivery and materiality of products. In this light, this paper will zoom into the furniture designs during post communism in Albania by exploring two principle paradigms vintage and retro. First this paper argues that furniture design and production in the centralized economy, are introduced within the vintage paradigm in post-communist. The data collecting through observation demonstrate a high level of interest for the retro design in a free market economy. As the result the paper suggest the local actors, businesses and academia to use and persist nostalgia and retro design in furniture and their component.
Keywords: vintage design, retro design, communist, post-communist.